Prevalence and risk factors for depression in factitious disorder: a systematic review - Comacchio, Carla; Misca, Delia Manuela; Bortoletto, Riccardo; Palese, Alvisa; Balestrieri, Matteo; Colizzi, Marco (Frontiers in Psychiatry, 2024)
Factitious disorder is characterized by a pattern of abnormal behavior in which patients deliberately produce, falsify, or exaggerate physical and/or psychological symptoms that have no, or little, organic basis, to assume the sick role. In the context of a factitious disorder, depression can be both a feigned disease and an associated comorbidity. We performed a systematic review to provide an overview of the relationship between factitious disorder and depression, describe the prevalence of depression in factitious disorder, and identify factors that can contribute to the development of depression in patients suffering from factitious disorder.A literature search was performed using the electronic databases PubMed, EMBASE and Cochrane Library following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were eligible for inclusion in this review if they investigated factitious disorder or Munchausen Syndrome with comorbid depression.Depression was found to be highly prevalent in factitious disorder, affecting around 30% of the samples. Risk factors for depression in factitious disorder included having suffered from childhood and adulthood traumatic experiences and having a history of psychosocial problems.The treatment of factitious disorder is challenging and requires a multidisciplinary team approach. Given the high levels of depression in patients with factitious disorder, we recommend to always screen for depression once a factitious disorder is diagnosed.